A Rare Case of Persistent Lactic Acidosis in the ICU: Glycogenic Hepatopathy and Mauriac Syndrome - Kirsten S. Deemer; George F. Alvarez (Case Reports in Critical Care)
Mauriac syndrome is a rare disorder that can present with the single feature of glycogenic hepatopathy in children and adults with poorly controlled diabetes mellitus. An often underrecognized finding of glycogenic hepatopathy is lactic acidosis and hyperlactatemia. Primary treatment of glycogenic hepatopathy is improved long-term blood glucose control. Resolution of symptoms and hepatomegaly will occur with improvement in hemoglobin A1C. We present here a case of a young adult female presenting to the intensive care unit with Mauriac syndrome. This case demonstrates exacerbation of lactic acidosis in a patient with glycogenic hepatopathy treated for diabetic ketoacidosis with high dose insulin and dextrose.